Multicolor foamed pearl wool and preparation process thereof

By modifying the optimized formula of raw materials such as polyethylene and nano-silica, and combining the technology of multi-layer distributors, multi-color foamed pearl cotton is prepared, which solves the problem of limited application of traditional pearl cotton in high-end packaging and decoration fields, and achieves the diversity of materials, improves mechanical properties and improves heat resistance.

CN119775652APending Publication Date: 2025-04-08HUIZHOUSHI XUTE PLASTIC ELECTRONIC TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411994574.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The application of traditional pearl cotton materials in high-end product packaging and decoration is limited by a single color and structure, which is difficult to meet the market's demand for personalized and diversified packaging. At the same time, the performance is insufficient in heavy object packaging, high temperature environments or under large stretching and tearing forces.

Method used

By modifying the optimized formula of raw materials such as polyethylene and nano-silica, and combining the technology of multi-layer distributors, multi-color foamed pearl cotton is prepared to achieve controllable color distribution, improved mechanical properties, and improved heat resistance and aesthetics.

Benefits of technology

It has achieved the diversity of materials, improved mechanical properties, improved heat resistance and aesthetics, and is suitable for high-end product packaging and decoration, as well as toy materials and other fields, meeting the needs of modern industry and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224318480000111
    Figure BDA0005224318480000111
Patent Text Reader

Abstract

The invention belongs to the technical field of packaging materials and toy materials, and particularly relates to multicolor foamed pearl wool and a preparation process thereof. The foamed pearl wool comprises the following raw materials in parts by weight: 100 parts of modified polyethylene, 6-12 parts of a foaming agent, 0.8-2 parts of a nucleating agent, 0.5-3 parts of color master batches, 0.2-1 part of an antioxidant, 0.2-1 part of a lubricant and 0.5-0.7 part of a functional auxiliary agent, and the color master batches comprise at least two color master batches with different colors. The preparation process of the foamed pearl wool comprises the steps of raw material mixing, plasticizing, mixing, multi-color distribution, extrusion, cooling and shaping and the like. According to the pearl wool prepared by the invention, controllable distribution and diversity of colors are realized, and meanwhile, the tensile strength, the tear strength and the heat resistance of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of packaging materials and toy materials, and particularly relates to multi-color foamed pearl cotton and a preparation process thereof. Background Art

[0002] With the rapid development of modern industry and the increasing requirements of consumers for product packaging, environmentally friendly, lightweight, and foam materials with good cushioning properties are becoming more and more popular in the market. Among many packaging materials, pearl cotton (EPE) has become a widely used packaging material in the electronics, home furnishing, toy and other industries due to its excellent impact resistance, heat preservation, and environmentally friendly recyclability. Pearl cotton is a material made of low-density polyethylene (LDPE) or linear low-density polyethylene (LLDPE) through physical foaming. Its interior is composed of countless independent bubbles, which give pearl cotton excellent cushioning properties and lightweight characteristics.

[0003] Despite the above advantages of pearl cotton, most traditional pearl cotton products are single-color, mainly white or transparent, which limits its application in high-end product packaging and decoration to a certain extent. In addition, a single color and structure are also difficult to meet the market's demand for personalized and diversified packaging. In order to break through this limitation, some colored pearl cotton products have appeared on the market, but most of these products are achieved through post-dyeing or printing, which not only increases production costs, but also may affect the environmental performance of the product due to the use of chemical dyes.

[0004] In addition, in certain specific application scenarios, such as heavy packaging, high temperature environment, or when large tensile and tearing forces are required, the performance of traditional pearl cotton is insufficient. Therefore, the market demand for pearl cotton with higher strength and better heat resistance is growing.

[0005] In summary, the development of a new type of multi-color foamed pearl cotton and its preparation process, on the basis of ensuring the original physical properties of the pearl cotton, realizes the controllable distribution of colors and the diversity of colors, while improving the tensile strength, tear strength and heat resistance of the material, reducing production costs, improving production efficiency, and reducing the impact on the environment, has important practical application value and broad market prospects. Summary of the invention

[0006] The purpose of the present invention is to provide a multi-color foamed pearl cotton and a preparation process thereof. The multi-color pearl cotton prepared by the present invention has excellent tensile strength, tear strength and heat resistance, and can meet the needs of modern industrial production and environmental protection.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] On the one hand, the present invention provides a multi-color foamed pearl cotton, comprising the following raw materials in parts by weight: 100 parts of modified polyethylene, 6 to 12 parts of foaming agent, 0.8 to 2 parts of nucleating agent, 0.5 to 3 parts of masterbatch, 0.2 to 1 part of antioxidant, 0.2 to 1 part of lubricant, and 0.5 to 0.7 parts of functional additives, wherein the masterbatch contains masterbatches of at least two different colors.

[0009] Furthermore, the modified polyethylene is obtained by modifying low-density polyethylene by maleic anhydride grafted polyethylene and a silane coupling agent.

[0010] Furthermore, the preparation method of the modified polyethylene comprises the following steps:

[0011] (a) adding maleic anhydride grafted polyethylene and a silane coupling agent to low-density polyethylene and stirring for 5 to 10 minutes, wherein the mass of the maleic anhydride grafted polyethylene is 4-6% of the mass of the low-density polyethylene, and the mass of the silane coupling agent is 0.5-2% of the mass of the low-density polyethylene;

[0012] (b) adding the mixed raw materials into a twin-screw extruder for melt kneading, and after the kneading is completed, extruding and granulating to obtain modified polyethylene.

[0013] Furthermore, the silane coupling agent is selected from any one of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane and vinyltriethoxysilane.

[0014] Traditional foaming pearl cotton generally adopts low-density polyethylene as matrix resin, and the prepared material usually has insufficient mechanical properties and poor processing performance. To solve this problem, the present invention modifies low-density polyethylene, and the modified polyethylene can significantly improve the interface compatibility and dispersibility of polyethylene with other additives (such as nucleating agent, antioxidant, lubricant, etc.) by introducing maleic anhydride grafted polyethylene and silane coupling agent. Maleic anhydride grafted polyethylene contains polar group carboxyl, which can form chemical bonds or physical adsorption with inorganic fillers in the material to enhance interfacial bonding. Silane coupling agent also has polar groups, which can react with the hydroxyl groups on the surface of inorganic fillers to form stable chemical bonds. The present invention also unexpectedly finds that the polyethylene after modification can provide more nucleation points, making the foam structure more fine and uniform during the foaming process.

[0015] Furthermore, the foaming agent is butane and carbon dioxide, and the mass ratio is 1:0.2-0.4.

[0016] Furthermore, the nucleating agent is surface-modified nano-silicon dioxide, talcum powder and mica powder, and the mass ratio is 1:0.1-0.5:0.1-0.5.

[0017] Furthermore, the preparation method of the surface-modified nano-silicon dioxide is as follows:

[0018] (i) weighing nano-silicon dioxide and hexadecyltrimethylammonium chloride in a mass ratio of 1:0.05-0.5, dispersing the nano-silicon dioxide in deionized water, stirring to form a suspension with a concentration of 1-3 wt %, and dissolving the hexadecyltrimethylammonium chloride in deionized water to form a solution with a concentration of 0.3-0.5 wt %;

[0019] (ii) adding the hexadecyltrimethylammonium chloride solution dropwise to the nano-silicon dioxide suspension while stirring at a stirring rate of 500 to 1000 rpm for 30 to 40 minutes to obtain a mixture;

[0020] (iii) heating the mixture obtained in step (ii) at 50 to 70° C. for 0.5 to 1.5 hours;

[0021] (iv) centrifuging the mixture after the heating treatment, collecting the precipitate, washing the precipitate with deionized water and ethanol for 1 to 3 times respectively, and drying the washed precipitate to obtain the surface-modified nano-silicon dioxide.

[0022] Nano-silicon dioxide, as a nucleating agent, can significantly improve the foam structure, making it more dense and uniform. Nano-silicon dioxide can also enhance the crystallinity of the matrix material and improve the mechanical strength and toughness of the material. However, the inventors found that the use of unmodified nano-silicon dioxide will cause it to easily agglomerate in the polymer matrix, forming large particles or lumps, resulting in uneven dispersion, which not only affects the uniformity of the foam structure, but also reduces the mechanical properties of the material; in addition, the interface compatibility of unmodified nano-silicon dioxide and the polymer matrix is ​​poor, and the interface bonding force is weak, which affects the effective transmission of stress, thereby reducing the overall mechanical properties of the material. Therefore, the inventors have surface-modified nano-silicon dioxide, and by introducing hydrophobic hexadecyltrimethylammonium chloride, its dispersibility in the polymer matrix can be significantly improved. Uniformly dispersed nano-silicon dioxide can provide more nucleation points, making the foam structure more dense and uniform, thereby improving the mechanical properties of the material. In addition, surface-modified nano-silicon dioxide has better thermal stability, can maintain good dispersibility and nucleation effect at high temperatures, thereby improving the heat resistance of the material.

[0023] Furthermore, the antioxidants are antioxidant 1010 and antioxidant 168, and the mass ratio is 1:0.5-1.5.

[0024] Furthermore, the lubricant is monoglyceride and polyethylene wax, and the mass ratio is 7-8:2-3.

[0025] Furthermore, the functional additives are nano titanium dioxide, zinc borate and lanthanum oxide, and the mass ratio is 1:0.3-0.6:0.05-0.2.

[0026] The invention adds a specific ratio of functional additives to the formula to significantly improve the mechanical strength and heat resistance of the material. In particular, the lanthanum oxide therein has extremely high thermal stability and can significantly improve the heat resistance of the material. However, when the amount of lanthanum oxide added is too much, it will affect the effects of nano titanium dioxide and zinc borate, resulting in a decrease in overall performance. Nano titanium dioxide, zinc borate and lanthanum oxide can synergistically improve the mechanical properties and heat resistance of the material under a specific ratio.

[0027] Another aspect of the present invention provides a method for preparing the multi-color foamed pearl cotton, comprising the following steps:

[0028] (1) The modified polyethylene, nucleating agent, antioxidant, lubricant and functional additive are weighed and divided into n parts, where n is equal to the number of colors of the masterbatch, and each part of the raw material is added with a masterbatch of different colors, and stirred for 5 to 10 minutes using a mixer (high-speed mixer) to obtain raw materials of different colors;

[0029] (2) using n twin-screw extruders, adding raw materials of different colors into different extruders respectively, plasticizing and mixing the raw materials, and adding a foaming agent into the plasticized raw materials through a metering pump in the plasticizing section of the barrel of each extruder, and mixing;

[0030] (3) The raw materials after plasticization and mixing are extruded from the die of each extruder, and the extruded materials enter the multi-layer distributor. The multi-layer distributor is provided with a plurality of independent flow channels, each flow channel corresponds to the die of an extruder, and materials of different colors are stacked in a predetermined order inside the multi-layer distributor. The stacked materials are extruded from the outlet of the multi-layer distributor, and the molten raw materials expand and form due to the loss of pressure;

[0031] (4) The extruded material enters a cooling device and is solidified by cooling (rapid cooling) to form a stable shape and size to obtain multi-color foamed pearl cotton.

[0032] Furthermore, the segmented temperature of the twin-screw extruder is controlled as follows: front section: 120-130°C, middle section: 135-145°C, rear section: 145-150°C; the rotation speed is 300-600 rpm.

[0033] Furthermore, the plasticizing and mixing time is 5 to 20 minutes.

[0034] Furthermore, the cooling temperature of the cooling device is controlled at 20-30° C., and the cooling time is 1-5 minutes.

[0035] The preparation process of the present invention uses a multi-layer distributor, which can ensure that materials of different colors are stacked in a predetermined order inside the multi-layer distributor to form a uniform and controllable multi-color layered structure. The design of the multi-layer distributor can avoid mixing between materials of different colors, ensure clear color boundaries, and improve the aesthetics of the material. The multi-layer distributor of the present invention has a simple structure, can be designed according to actual needs, and can also be directly purchased, and brightly colored multi-color foamed pearl cotton can be obtained without complex processes and expensive costs.

[0036] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0037] The invention provides a multicolor foamed pearl cotton and a preparation process thereof, which significantly improves the comprehensive performance of the material by optimizing the raw material selection and preparation method. The addition of modified polyethylene in the formula not only improves the mechanical properties of the material, but also makes the foaming material more uniform and fine. The addition of surface-modified nano-silicon dioxide also improves the fine uniformity of the foam structure, and also enhances the crystallinity and mechanical strength of the matrix material, effectively avoiding the problem of easy agglomeration and poor interface compatibility of unmodified nano-silicon dioxide. Butane and carbon dioxide are selected as foaming agents to ensure the fine uniformity of the pores and improve the tensile strength and tear resistance of the material. The reasonable ratio of functional additives nano-titanium dioxide, zinc borate and lanthanum oxide further enhances the mechanical properties and heat resistance of the material. In addition, the use of a multi-layer distributor ensures the controllable stacking of materials of different colors, the color boundary is clear, and the aesthetics and application range of the material are improved. Overall, the multicolor foamed pearl cotton of the present invention has excellent mechanical properties, heat resistance and aesthetics, is suitable for high-end product packaging and decoration, and toy materials and other fields, and meets the needs of modern industry and environmental protection. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Unless otherwise specified, the raw materials used in the examples are all common commercially available products. The following is an exemplary description:

[0040] Nano-silica was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with an average particle size of 10 nm;

[0041] Low-density polyethylene was purchased from Sinopec, LDPE 2426H;

[0042] Maleic anhydride grafted polyethylene was purchased from Sinopec, PE-g-MAH 1000;

[0043] Talc powder was purchased from Liaoning Talc Mine Co., Ltd., with an average particle size of 3 μm;

[0044] Mica powder was purchased from Sichuan Mica New Materials Co., Ltd., with an average particle size of 44-74 μm;

[0045] Red masterbatch was purchased from Zhejiang Wankai New Materials Co., Ltd., RK-100R;

[0046] Yellow masterbatch was purchased from Jiangsu Jinfa Technology Development Co., Ltd., JF-100Y;

[0047] Blue masterbatch was purchased from Guangdong Liansu Technology Industry Co., Ltd., LS-100B;

[0048] Lanthanum oxide was purchased from Hunan Rare Earth Metal Materials Research Institute;

[0049] Sorbitan monooleate was purchased from Shandong Luxi Chemical Group Co., Ltd., SPAN 80;

[0050] Mica powder was purchased from Liaoning Jinhui Mining Co., Ltd., with an average particle size of 3 μm;

[0051] Montmorillonite was purchased from Hubei Hongyuan Mining Resources Development Co., Ltd. with an average particle size of 3 μm.

[0052] The multicolor distributor used in the embodiment is equipped with multiple inlets, each of which corresponds to a twin-screw extruder, and each inlet is connected to the corresponding extruder die through a pipeline to ensure that the material can smoothly enter the distributor. The distributor is designed with multiple independent flow channels, each of which corresponds to an inlet to ensure that materials of different colors will not mix after entering the distributor. A common outlet is provided at the end of the distributor, where all materials of different colors converge and stack together to form a molten material with a multicolor layered structure. The multicolor distributor can be designed as needed or purchased directly. The multicolor distributor used in the embodiment of the present invention was purchased from Brabender, Germany, and the model is Brabender Multi-Layer Coextrus ion Die.

[0053] Example 1

[0054] This embodiment provides a surface-modified nano-silicon dioxide, the preparation method of which comprises the following steps:

[0055] (i) weighing nano-silicon dioxide and hexadecyltrimethylammonium chloride in a mass ratio of 1:0.1, dispersing the nano-silicon dioxide in deionized water, stirring to form a suspension with a concentration of 2 wt %, and dissolving the hexadecyltrimethylammonium chloride in deionized water to form a solution with a concentration of 0.4 wt %;

[0056] (ii) adding the hexadecyltrimethylammonium chloride solution dropwise to the nano-silicon dioxide suspension while stirring at a stirring rate of 800 rpm for 35 minutes to obtain a mixture;

[0057] (iii) heating the mixture obtained in step (ii) in a water bath at 60° C. for 1 hour;

[0058] (iv) centrifuging the mixture after the heating treatment at a speed of 3000 rpm for 10 minutes, collecting the precipitate, washing the precipitate twice with deionized water and ethanol respectively, and drying the washed precipitate at 60° C. to constant weight to obtain the surface-modified nano-silica.

[0059] Example 2

[0060] This embodiment provides a method for preparing modified polyethylene, comprising the following steps:

[0061] (a) adding 5% of the mass of the low-density polyethylene by weight of maleic anhydride grafted polyethylene and 1% of the mass of the low-density polyethylene by weight of a silane coupling agent (γ-aminopropyltriethoxysilane) to the low-density polyethylene and stirring for 10 minutes;

[0062] (b) adding the mixed raw materials into a twin-screw extruder for melt mixing, controlling the segmented temperatures of the twin-screw extruder as follows: 125° C. for the front section, 140° C. for the middle section, and 150° C. for the rear section, and the screw speed is 500 rpm. After mixing, extrusion and granulation are performed to obtain modified polyethylene.

[0063] Example 3

[0064] This embodiment provides a multi-color foamed pearl cotton, which includes the following raw materials in parts by weight: 100 parts of modified polyethylene, 10 parts of foaming agent, 1 part of nucleating agent, 2 parts of masterbatch, 0.5 parts of antioxidant, 0.5 parts of lubricant, and 0.6 parts of functional additives;

[0065] The modified polyethylene is prepared according to the method of Example 2;

[0066] The foaming agent is butane and carbon dioxide, with a mass ratio of 1:0.3;

[0067] The nucleating agent is surface-modified nano-silicon dioxide, talcum powder and mica powder in a mass ratio of 1:0.2:0.3, wherein the surface-modified nano-silicon dioxide is prepared according to the method of Example 1;

[0068] The masterbatch comprises red masterbatch, yellow masterbatch and blue masterbatch, and the mass ratio is 1:1:1;

[0069] The antioxidants are antioxidant 1010 and antioxidant 168, with a mass ratio of 1:1;

[0070] The lubricant is monoglyceride and polyethylene wax, with a mass ratio of 7:3;

[0071] The functional additives are nano titanium dioxide, zinc borate and lanthanum oxide, with a mass ratio of 1:0.5:0.1;

[0072] The preparation method of the multi-color foamed pearl cotton comprises the following steps:

[0073] (1) The modified polyethylene, the nucleating agent, the antioxidant, the lubricant and the functional additive are weighed and divided into three equal parts, and a masterbatch of different colors is added to each raw material. After mixing, the mixture is stirred for 7 minutes using a high-speed stirrer to obtain three raw material mixtures of different colors;

[0074] (2) using three twin-screw extruders, adding three colors of raw materials into different extruders respectively, plasticizing and mixing the raw materials, controlling the segmented temperatures of the twin-screw extruders as follows: 125° C. for the front section, 140° C. for the middle section, and 145° C. for the rear section, and setting the screw speed to 400 rpm. In the plasticizing section of the barrel of each extruder, adding a foaming agent to the plasticized raw materials through a metering pump and mixing them thoroughly;

[0075] (3) The three color raw materials after plasticization and mixing are extruded from the die of their respective extruders and enter a multi-layer distributor. The multi-layer distributor is provided with three independent flow channels, each flow channel corresponds to the die of an extruder. The materials of different colors are stacked in a predetermined order inside the multi-layer distributor. The stacked materials are extruded from the outlet of the multi-layer distributor. The molten raw materials expand and form due to the loss of pressure;

[0076] (4) The extruded material immediately enters the cooling device, and the cooling temperature is controlled to be 25° C. The cooling time is set to 3 minutes to ensure that the material is quickly solidified and forms a stable shape and size. The multi-color foamed pearl cotton quilt after cooling and finalization is cut into the required specifications to complete the preparation.

[0077] In this embodiment, foamed pearl cotton in three colors of red, yellow and blue is prepared. The foamed pearl cotton presents a distinct layered structure, each layer has a clear color boundary, the transition between layers is smooth, and there is no obvious color mixing phenomenon.

[0078] Comparative Example 1

[0079] This comparative example provides a multi-color foamed pearl cotton, which is different from Example 3 in that the nano-silicon dioxide is not surface-modified.

[0080] Comparative Example 2

[0081] This comparative example provides a multi-color foamed pearl cotton, which is different from Example 3 in that the nucleating agent is sorbitan monooleate, mica powder and montmorillonite, and the mass ratio is 1:0.2:0.3.

[0082] Comparative Example 3

[0083] This comparative example provides a multi-color foamed pearl cotton, which is different from Example 3 in that the functional additives are nano titanium dioxide, zinc borate and lanthanum oxide, and the mass ratio is 1:0.1:0.5.

[0084] Comparative Example 4

[0085] This comparative example provides a multi-color foamed pearl cotton, which is different from Example 3 in that the functional additives are nano titanium dioxide, zinc borate and aluminum oxide, and the mass ratio is 1:0.5:0.1.

[0086] Comparative Example 5

[0087] This comparative example provides a multi-color foamed pearl cotton, which is different from Example 3 in that the foaming agent is azodicarbonamide.

[0088] Comparative Example 6

[0089] This comparative example provides a multi-color foamed pearl cotton, which is different from Example 3 in that the modified polyethylene is replaced by low-density polyethylene.

[0090] Performance Testing

[0091] The tensile strength, tear strength and heat resistance of the multi-color foamed pearl cotton prepared in Example 3 and Comparative Examples 1 to 6 were tested. The tensile strength was tested according to GB / T 1040.3-2006, the tear strength was tested according to GB / T 16578.1-2009, and the heat resistance was tested according to GB / T 7141-2008.

[0092] The test results are shown in Table 1.

[0093] Table 1 Performance test results

[0094]

[0095] As can be seen from the above performance test results, the multicolor foamed pearl cotton prepared by the present invention has excellent tensile strength, tear strength and heat resistance. In comparative example 1, nano silicon dioxide is not surface modified, and the surface-modified nano silicon dioxide can significantly improve its dispersibility and compatibility in the polymer matrix by introducing hydrophobic hexadecyltrimethylammonium chloride, while the unmodified nano silicon dioxide is easy to agglomerate, resulting in uneven dispersion, thereby affecting the mechanical properties of the material. In comparative example 2, the nucleating agent is sorbitan monooleate, mica powder and montmorillonite, and the selection of the nucleating agent directly affects the structure and uniformity of the foam. After the nucleating agent is replaced, the pore size is different, and the foam structure is uneven, thereby affecting the mechanical properties of the material. In comparative example 3, the proportion of functional additives is changed, especially the proportion of lanthanum oxide is too high. Although lanthanum oxide can improve heat resistance, too high a proportion may interfere with the effect of nano titanium dioxide and zinc borate, resulting in overall performance degradation, and this unbalanced proportion leads to a decrease in the mechanical properties and heat resistance of the material. In Comparative Example 4, lanthanum oxide is replaced by aluminum oxide. Although aluminum oxide has a certain reinforcing effect, its thermal stability and mechanical properties are not as good as those of lanthanum oxide. Therefore, the use of aluminum oxide instead of lanthanum oxide will lead to a decrease in the heat resistance and mechanical properties of the material. In Comparative Example 5, the foaming agent is replaced by azodicarbonamide. Azodicarbonamide is a common chemical foaming agent, but it is not applicable in the specific formula of the present invention. The pore structure obtained by foaming with azodicarbonamide is large and uneven, resulting in a decrease in the tensile strength and tear strength of the material. In Comparative Example 6, the modified polyethylene is replaced by low-density polyethylene. Because the unmodified low-density polyethylene lacks polar groups, the interface compatibility and dispersibility are poor, so the mechanical properties and heat resistance are poor.

[0096] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A multi-color foamed pearl cotton, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of modified polyethylene, 6 to 12 parts of foaming agent, 0.8 to 2 parts of nucleating agent, 0.5 to 3 parts of masterbatch, 0.2 to 1 part of antioxidant, 0.2 to 1 part of lubricant and 0.5 to 0.7 parts of functional additive, wherein the masterbatch comprises masterbatches of at least two different colors.

2. The multicolor foamed pearl cotton according to claim 1, characterized in that: The modified polyethylene is obtained by modifying low-density polyethylene through maleic anhydride grafted polyethylene and a silane coupling agent.

3. The multi-color foamed pearl cotton according to claim 2, characterized in that: The preparation method of the modified polyethylene comprises the following steps: (a) adding maleic anhydride grafted polyethylene and a silane coupling agent to low-density polyethylene and stirring for 5 to 10 minutes, wherein the mass of the maleic anhydride grafted polyethylene is 4-6% of the mass of the low-density polyethylene, and the mass of the silane coupling agent is 0.5-2% of the mass of the low-density polyethylene; (b) adding the mixed raw materials into a twin-screw extruder for melt kneading, and after the kneading is completed, extruding and granulating to obtain modified polyethylene.

4. The multi-color foamed pearl cotton according to claim 1, characterized in that: The foaming agent is butane and carbon dioxide, and the mass ratio is 1:0.2-0.

4.

5. The multi-color foamed pearl cotton according to claim 1, characterized in that: The nucleating agent is surface-modified nano-silicon dioxide, talcum powder and mica powder, with a mass ratio of 1:0.1-0.5:0.1-0.

5. The preparation method of the surface-modified nano-silicon dioxide is as follows: (i) weighing nano-silicon dioxide and hexadecyltrimethylammonium chloride in a mass ratio of 1:0.05-0.5, dispersing the nano-silicon dioxide in deionized water, stirring to form a suspension with a concentration of 1-3 wt %, and dissolving the hexadecyltrimethylammonium chloride in deionized water to form a solution with a concentration of 0.3-0.5 wt %; (ii) adding the hexadecyltrimethylammonium chloride solution dropwise to the nano-silicon dioxide suspension while stirring at a stirring rate of 500 to 1000 rpm for 30 to 40 minutes to obtain a mixture; (iii) heating the mixture obtained in step (ii) at 50 to 70° C. for 0.5 to 1.5 hours; (iv) centrifuging the mixture after the heating treatment, collecting the precipitate, washing the precipitate with deionized water and ethanol for 1 to 3 times respectively, and drying the washed precipitate to obtain the surface-modified nano-silicon dioxide.

6. The multi-color foamed pearl cotton according to claim 1, characterized in that: The antioxidants are antioxidant 1010 and antioxidant 168, and the mass ratio is 1:0.5-1.

5.

7. The multi-color foamed pearl cotton according to claim 1, characterized in that: The lubricant is monoglyceride and polyethylene wax, and the mass ratio is 7-8:2-3.

8. The multi-color foamed pearl cotton according to claim 1, characterized in that: The functional additives are nano titanium dioxide, zinc borate and lanthanum oxide, and the mass ratio is 1:0.3-0.6:0.05-0.

2.

9. The method for preparing the multicolor foamed pearl cotton according to any one of claims 1 to 8, comprising the following steps: (1) The modified polyethylene, nucleating agent, antioxidant, lubricant and functional additive are weighed and divided into n parts, where n is equal to the number of colors of the masterbatch, and different colors of masterbatch are added to each part of the raw materials, and stirred for 5 to 10 minutes using a mixer to obtain raw materials of different colors; (2) using n twin-screw extruders, adding raw materials of different colors into different extruders respectively, plasticizing and mixing the raw materials, and adding a foaming agent into the plasticized raw materials through a metering pump in the plasticizing section of the barrel of each extruder, and mixing; (3) The raw materials after plasticization and mixing are extruded from the die of each extruder, and the extruded materials enter the multi-layer distributor. The multi-layer distributor is provided with a plurality of independent flow channels, each flow channel corresponds to the die of an extruder, and materials of different colors are stacked in a predetermined order inside the multi-layer distributor. The stacked materials are extruded from the outlet of the multi-layer distributor, and the molten raw materials expand and form due to the loss of pressure; (4) The extruded material enters a cooling device and solidifies by cooling to form a stable shape and size to obtain multi-color foamed pearl cotton.

10. The preparation method according to claim 9, characterized in that: The plasticizing and mixing time is 5 to 20 minutes, the cooling temperature of the cooling device is controlled at 20 to 30° C., and the cooling time is 1 to 5 minutes.

Citation Information

Patent Citations

  • Preparation method of pearl wool packaging material

    CN101717535A

  • Modified polyethylene for supercritical CO2 foaming and preparation method thereof

    CN102775671A

  • Environment-friendly single EPE sheet with high foaming capacity

    CN102850620A

  • EPE pearl wool material and preparation method thereof

    CN109485977A

  • Easily melted foamed polyethylene bead with strong temperature tolerance and preparation method thereof

    CN109651695A